The image of a woman in the works of the korean poetess Kim Hye Sung (Journal of Oriental Studies, 2019)
The vigorous interest of critics and the general literary community towards female poetic creativity in Korea since the late 1960s led to an increase in the number of women poets. Despite the fact that it has been a long time since Korean society stood on the European path of development, the theme of oppression of women’s society is still relevant today. The purpose of this study is to study the image and position of women in modern Korean society on the example of the work of the Korean poetess Kim Hye Sung. This article uses a biographical method, as well as a theological analysis in the aspect of structural poetics, with the help of which it is revealed how a poetess describes the lifestyle of a modern Korean woman. The scientific significance of the work lies in the fact that its results can serve as a basis for further research on the themes and poetics of modern Korean female poetry, still little studied both in Korea and in Kazakhstan. The methodological basis of the study are the work of Korean and foreign literary scholars on the analysis of Korean female poetry in general, and, in particular, the poetry of Kim Hye Sung, such as Choi Don Mi, Bruce Fulton, Helen Koh, Ko Yon Chol, Lee Yu Rem, Choi Yu Mi and many others. The results of the study of the work of the poetess led to the conclusion that contemporary Korean female poetry is still characterized by feminist features. The poetess speaks not only for herself, but also for so many women who are facing injustice in the modern world. Key words: Korean women’s poetry, feminism, grotesque, absurd, symbolic image.